2021
DOI: 10.1099/mgen.0.000533
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive in silico survey of the Mycolicibacterium mobilome reveals an as yet underexplored diversity

Abstract: The mobilome plays a crucial role in bacterial adaptation and is therefore a starting point to understand and establish the gene flow occurring in the process of bacterial evolution. This is even more so if we consider that the mobilome of environmental bacteria can be the reservoir of genes that may later appear in the clinic. Recently, new genera have been proposed in the family Mycobacteriaceae , including the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 121 publications
(174 reference statements)
1
17
0
Order By: Relevance
“…In fact, a previous survey of Mycolicibacterium mobilome showed an 8 kb non-mobilisable plasmid, without association to any ARG, shared by two M. fortuitum metagenomes (SCH6189132/cluster II/ South Africa and MTB7/cluster III/Morocco). (18) The M. fortuitum virulome was accessed using ABRicate based on Virulence Factor Database. Four genes were identified in all genomes: icl, ideR, phoP, and relA (except relA in GA-0871).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a previous survey of Mycolicibacterium mobilome showed an 8 kb non-mobilisable plasmid, without association to any ARG, shared by two M. fortuitum metagenomes (SCH6189132/cluster II/ South Africa and MTB7/cluster III/Morocco). (18) The M. fortuitum virulome was accessed using ABRicate based on Virulence Factor Database. Four genes were identified in all genomes: icl, ideR, phoP, and relA (except relA in GA-0871).…”
Section: Resultsmentioning
confidence: 99%
“…Resistome and virulome analysis -M. fortuitum genomes were surveyed for antibiotic resistance and virulence genes through ABRicate (https://github.com/tseemann/abricate) based on The Comprehensive Antibiotic Resistance Database (16) and Virulence Factor Database. (17) In addition, T7SS was searched based on the identification of the T7SS core proteins (18) using HMMer package v3.1b2. (19)…”
Section: Methodsmentioning
confidence: 99%
“…Through genomic analysis, we identified several genes on the chromosome associated with antibiotic resistance, suggesting that they are inherent to this organism and not related to plasmid-mediated acquisition. Indeed, in a previous in silico study of Mycolicibacterium plasmids, no notable antibiotic resistance genes were observed in plasmids of M. fortuitum [ 23 ]. Another aspect verified in the genome of the 7G strain was the type VII, present in four loci and reported to be associated with virulence, iron uptake and conjugation in several species of the Mycobacteriaceae family [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids that encoded a relaxase gene and that did not encode VirB4 and/or VirD4 were considered mobilizable, while those encoding relaxase, VirB4, and VirD4 were considered conjugative. Plasmids lacking relaxases were considered incapable of self-mobilization, non-mobilizable 42 , 44 . However, it is possible that unknown origin of transfer (oriT) sequences are present in these plasmids, which would allow their mobilization only in a relaxase- in trans mechanism 46 , 47 .…”
Section: Methodsmentioning
confidence: 99%